2017
DOI: 10.1136/bjsports-2016-097352
|View full text |Cite
|
Sign up to set email alerts
|

Does leisure time physical activity protect against low back pain? Systematic review and meta-analysis of 36 prospective cohort studies

Abstract: background There are plausible mechanisms whereby leisure time physical activity may protect against low back pain (LBP) but there have been no quality systematic reviews and meta-analyses of the subject. Objective This review aims to assess the effect of leisure time physical activity on non-specific LBP. Methods Literature searches were conducted in PubMed, Embase, Web of Science, Scopus and Google Scholar databases from their inception through July 2016. Methodological quality of included studies was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
158
10
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 186 publications
(197 citation statements)
references
References 81 publications
15
158
10
14
Order By: Relevance
“…Additionally, we found that walking or cycling to work, independent of body weight and other leisure activities, protects against hospitalization for sciatica. In our earlier meta-analyses 13,26 we found that moderate or high level of leisure-time physical activity protects against lumbar radicular pain 13 and chronic low back pain 26 by 11%-16% only, supporting the current result that the protective effects of physical activity on most low back outcomes are minor.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, we found that walking or cycling to work, independent of body weight and other leisure activities, protects against hospitalization for sciatica. In our earlier meta-analyses 13,26 we found that moderate or high level of leisure-time physical activity protects against lumbar radicular pain 13 and chronic low back pain 26 by 11%-16% only, supporting the current result that the protective effects of physical activity on most low back outcomes are minor.…”
Section: Discussionsupporting
confidence: 76%
“…Many systematic reviews have reported on the low quality of evidence concerning the relationship between musculoskeletal disease symptoms and physical activity level. Unfortunately, most studies have focused on generalized pain disorders including fibromyalgia and localized disorders of other body parts including the lower back, neck and shoulders . No study has considered the relationship between general physical activity level and TMD symptoms before, and this is the first attempt to define such an association.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise effectively reduces pain symptoms, even in patients with chronic pain disorders such as fibromyalgia and lower back pain . However, clinical observations also suggest that many patients with musculoskeletal pain experience an increase in pain and fatigue during exercise or even while conducting simple daily activities …”
Section: Introductionmentioning
confidence: 99%
“…A protective effect of exercise against LBP during pregnancy is plausible, given its effects on LBP in non-pregnant women (Shiri et al, 2016;Steffens et al, 2016;Shiri and Falah-Hassani, 2017), and also limited evidence of benefits in the treatment of LBP during pregnancy (Liddle and Pennick, 2015;Kinser et al, 2017). Furthermore, a prospective cohort study of 2753 pregnant women found that moderate or high level of physical activity was associated with a 10% reduction in new episodes of low back pain after adjustment for age, parity, education, smoking, pre-pregnancy body mass index and low back pain before the current pregnancy (Gjestland et al, 2013).…”
Section: Discussionmentioning
confidence: 99%